Green Organizational Culture, Green Work Engagement, and Green Human Resources Management as The Anticedents of Employee Green Behavior in Indonesia's State-Owned Construction Industry - Prasetyo, Dwi Wahyu; Febryan Maula, Ince Suil; Margaliu, Muhammad Fikrinala; Rohman, Abdul (Management Analysis Journal, 2025)
This research is motivated by the importance of promoting environmentally friendly behavior (Employee Green Behavior) in the state-owned construction service industry. The study aims to examine the influence of Green Organizational Culture (GOC), Green Work Engagement (GWE) and Green Human Resource Management (GHRM) as the antecedent of EGB. The research methodology employs a quantitative approach through surveys conducted with employees of construction service companies under state-owned enterprises (BUMN). The sampling technique used in this study is simple random sampling, involving a total of 386 permanent employees from construction companies. The analysis method utilized in this research is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), using the SmartPLS 3.0 analysis tool. The results indicate that GHRM, GOC, and GWE directly influence EGB. These findings reinforce the AMO and NAM theories. This research contributes theoretically to the literature on sustainable human resource management and provides practical benefits for companies sustainable strategies.